PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN KARAKTERISTIK INDIVIDU TERHADAP KINERJA KARYAWAN PADA PT. BANK BPD CABANG RENON DENPASAR - I Gusti Agung Hendra Wirawan; I Nengah Suardhika; I Gede Yudhi Hendrawan (EMAS, 2021)
The purpose of this study was to determine the influence of organizational culture, leadership, individual characteristics on employee performance at PT. BANK BPD Renon Denpasar Branch. Data collection methods used in this study were questionnaire methods, documentation and interviews. The population and sample in this study were all employees of the Bank BPD Renon Denpasar branch, in order to minimize the level of error when making generalizations, the sample used in this study was 64 employees in RSPAM, OB and cleaning service using a questionnaire with 18 questions. The data analysis techniques used were validity test, rehabilitation test, descriptive analysis, inferential analysis, classical assumption test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, t test and f test. The results of this study indicate that the variables of organizational culture, leadership, individual characteristics have a positive and significant effect on employee performance. organizational culture, leadership, good individual characteristics will improve employee performance